Chronic Kidney Disease Induces Inflammatory CD40+ Monocyte Differentiation via Homocysteine Elevation and DNA Hypomethylation - Yang, Jiyeon; Fang, Pu; Yu, Daohai; Zhang, Lixiao; Zhang, Daqing; Jiang, Xiaohua; Yang, William Y.; Bottiglieri, Teodoro; Kunapuli, Satya P.; Yu, Jun; Choi, Eric T.; Ji, Yong; et al. (Circulation research, 2016)
RATIONALE:Patients with chronic kidney disease (CKD) develop hyperhomocysteinemia and have a higher cardiovascular mortality than those without hyperhomocysteinemia by 10-fold. OBJECTIVE:We investigated monocyte differentiation in human CKD and cardiovascular disease (CVD). METHODS AND RESULTS:We identified CD40 as a CKD-related monocyte activation gene using CKD-monocyte -mRNA array analysis and classified CD40 monocyte (CD40CD14) as a stronger inflammatory subset than the intermediate monocyte (CD14CD16) subset. We recruited 27 patients with CVD/CKD and 14 healthy subjects and found that CD40/CD40 classical/CD40 intermediate monocyte (CD40CD14/CD40CD14CD16/CD40CD14CD16), plasma homocysteine, S-adenosylhomocysteine, and S-adenosylmethionine levels were higher in CVD and further elevated in CVD+CKD. CD40 and CD40 intermediate subsets were positively correlated with plasma/cellular homocysteine levels, S-adenosylhomocysteine and S-adenosylmethionine but negatively correlated with estimated glomerular filtration rate. Hyperhomocysteinemia was established as a likely mediator for CKD-induced CD40 intermediate monocyte, and reduced S-adenosylhomocysteine/S-adenosylmethionine was established for CKD-induced CD40/CD40 intermediate monocyte. Soluble CD40 ligand, tumor necrosis factor (TNF)-α/interleukin (IL)-6/interferon (IFN)-γ levels were elevated in CVD/CKD. CKD serum/homocysteine/CD40L/increased TNF-α/IL-6/IFN-γ–induced CD40/CD40 intermediate monocyte in peripheral blood monocyte. Homocysteine and CKD serum-induced CD40 monocyte were prevented by neutralizing antibodies against CD40L/TNF-α/IL-6. DNA hypomethylation was found on nuclear factor-κB consensus element in CD40 promoter in white blood cells from patients with CKD with lower S-adenosylmethionine / S-adenosylhomocysteine ratios. Finally, homocysteine inhibited DNA methyltransferase-1 activity and promoted CD40 intermediate monocyte differentiation, which was reversed by folic acid in peripheral blood monocyte. CONCLUSIONS:CD40 monocyte is a novel inflammatory monocyte subset that appears to be a biomarker for CKD severity. Hyperhomocysteinemia mediates CD40 monocyte differentiation via soluble CD40 ligand induction and CD40 DNA hypomethylation in CKD.